Case report: Coexistence of Labbe vein thrombosis and autoimmune encephalitis with two different antibodies - Yang, Lu; Zhang, Dongqing (Frontiers in Neurology, 2023)
Anti-NMDA receptor encephalitis is an autoimmune encephalitis well- known to pediatric neurologists. The characteristic combination of symptoms and detection of NMDA receptor antibody can confirm the diagnosis. Most children respond well to immunosuppressive therapy. Anti-GABAB receptor encephalitis usually occurs in adult patients. Most patients present clinically with symptoms of limbic encephalitis. Cases in pediatric patients are rare. Cerebral venous thrombosis also has a very low incidence in children without underlying diseases. Patients usually present with headaches, convulsions, and focal deficits. Anticoagulants are the first choice treatment. We report a boy initially diagnosed with Labbe vein thrombosis and later tested positive for both NMDA and GABAB receptors. Anticoagulants did not relieve the boy's symptoms, and immunosuppressive therapy achieved good results. The antibody titers were significantly reduced or even turned negative. Although the Labbe vein was not recanalized at four months follow-up, the brain lesion was significantly absorbed. We learn from this case that a child can be inflicted with cerebral venous thrombosis and autoimmune encephalitis simultaneously. Child patients respond well to treatment.